Treecube: Visualization Tool for Browsing 3D Multimedia Data - Tanaka, Yoichi; Okada, Yoshihiro; Niijima, Koichi (IV'03: Proceedings of the International Conference on Information Visualisation, 2003)
This paper proposes a new 3D visualization tool for hierarchical information. A 2D visualization tool for hierarchical information called treemap has already been proposed by Ben Shneiderman, et al. in 1992. In general, hierarchical information is represented as a tree structure. Treemap hierarchically lays out each node as a bounding box, whose size is the same as the specific weight or attribute value of the node. After the original treemap algorithm called slice-and-dice, some extensions to it have been proposed: squarified treemap, ordered treemap and strip treemap. Furthermore, quantum treemap is a quantization version of these extensions. In this paper, the authors propose a new 3D visualization tool for hierarchical information called treecube that can be taken as a 3D extension of treemap. Especially, this paper shows its usefulness for browsing 3D multimedia data, i.e., 2D images, 3D shape models, motion data, etc., originally stored in a file system.